Effect of the different printing patterns of graphene nanoparticles in conductive ink on electrical and mechanical performance - Salim, Mohd Azli; Md. Saad, Adzni; Ahmad, Fauzi; Akop, Mohd Zaid; Al-Mola, Mohammed Hussin A.; Saad, Hartini (Penerbit UniMAP, 2021)
The utilization of graphene in the formation of conductive ink has been positively accepted by the electronics industry especially with the emerging of printable and flexible electronics. Because of that, it motivates this study to investigate the electrical, mechanical, and morphological properties for different patterns of Graphene Nanoparticle (GNP) conductive ink. The samples were prepared using the screen-printing technique with a low annealing temperature of 100 ºC for 30 minutes. The investigated parameter for the electrical property was the sheet resistivity, which showed that the zigzag pattern recorded the highest value of 1.077 kΩ/sq at the 3 mm of ink thickness. For the mechanical properties, the highest of hardness for 2 mm thickness was the curve pattern and for 3 mm was the square pattern, with the values of 3.849 GPa and 4.913 GPa. Both maximum values showed a direct correlation with the behavior of the elastic modulus of the ink. The maximum values of elastic modulus were recorded at the same ink pattern and thickness. For the morphological analysis, the surface roughness and qualitative analysis using SEM images were performed. The surface roughness showed that the increase of GNP in the composition increased the surface roughness because it decreased the homogeneity of the mixture. The recorded SEM images of the ink layer microstructure surface showed a direct correlation with the obtained sheet resistivity data. The samples that produced high sheet resistivity showed the presence of bumps, creases, and defects on the ink layer surface. Based on the obtained data, the correlation between electrical, mechanical, and morphological properties can be established for the GNP conductive ink with various patterns and thicknesses.